Digital Literacy as a Strategy for Preventing and Handling Sexual Violence in the Indonesian Academic Communities - Mite Setiansah; Nuryanti; Edi Santoso; Tri Wuryaningsih (Comunicação e Sociedade)
Sexual violence in universities represents an iceberg phenomenon. The Indonesian Ministry of Research, Technology, and Higher Education has identified sexual violence as one of the most serious issues facing higher education. In response, the ministry enacted a regulation to address the prevention and handling of sexual violence (PHSV) within universities. While there is extensive research on the implementation of this regulation, as well as on the controversies surrounding it and the handling of sexual violence cases in universities, limited studies have explored the association between the prevention and management of such cases and the digital literacy levels among university community members. On the other hand, socialization and prevention programs related to sexual violence are mostly conducted through digital media platforms. This study employed qualitative research methods to assess the digital literacy levels of university community members in relation to PHSV. Initial data was collected through questionnaires, focus group discussions, and documentation of informants. The findings highlight that preventing and addressing sexual violence cannot be effectively achieved solely by disseminating PHSV information via digital media. These efforts must be supported by initiatives to enhance digital literacy across university communities. This research provides valuable insights into the intersection of digital literacy and gender-based violence prevention, particularly in academic settings. Methodologically, the study demonstrates the adequacy of the qualitative approaches in comprehensively exploring and describing this phenomenon. Moreover, the study contributes to the broader academic discourse by illustrating how social and digital media shape perceptions of sexual violence and play a critical role in raising awareness.